Initial clinical experience of patient-specific QA of treatment delivery in online adaptive radiotherapy using a 1.5 T MR-Linac. (30th April 2021) - Yang, B; Wong, Y S; Lam, W W; Geng, H; Huang, C Y; Tang, K K; Law, W K; Ho, C C; Nam, P H; Cheung, K Y; Yu, S K
Abstract: Purpose . This study aims to evaluate the performance of a commercial 1.5 T MR-Linac by analyzing its patient-specific quality assurance (QA) data collected during one full year of clinical operation. Methods and Materials . The patient-specific QA system consisted of offline delivery QA (DQA) and online calculation-based QA. Offline DQA was based on ArcCHECK-MR combined with an ionization chamber. Online QA was performed using RadCalc that calculated and compared the point dose calculation with the treatment planning system (TPS). A total of 24 patients with 189 treatment fractions were enrolled in this study. Gamma analysis was performed and the threshold that encompassed 95% of QA results (T95) was reported. The plan complexity metric was calculated for each plan and compared with the dose measurements to determine whether any correlation existed. Results . All point dose measurements were within 5% deviation. The mean gamma passing rates of the group data were found to be 96.8 ± 4.0% and 99.6 ± 0.7% with criteria of 2%/2mm and 3%/3mm, respectively. T95 of 87.4% and 98.2% was reported for the overall group with the two passing criteria, respectively. No statistically significant difference was found between adaptive treatments with adapt-to-position (ATP) and adapt-to-shape (ATS), whilst the category of pelvis data showed a better passing rate than other sites. Online QA gave a mean deviation of 0.2 ± 2.2%. The plan complexity metric was positively correlated with the mean dose difference whilst the complexity of the ATS cohort had larger variations than the ATP cohort. Conclusions . A patient-specific QA system based on ArcCHECK-MR, solid phantom and ionization chamber has been well established and implemented for validation of treatment delivery of a 1.5 T MR-Linac. Our QA data obtained over one year confirms that good agreement between TPS calculation and treatment delivery was achieved.